Genotyping and Antimicrobial Susceptibility of Carbapenem-resistant Acinetobacter baumannii: ISAba-1-blaOXA-23 association and plasmid analysis - Mansour, Wejdene; Charfi, Karama; Grami, Raoudha; Massaoudi, Aziza; Ben Romdhane, Tounes; El Ahmer, Ikram; Bel Haj Khlifa, Anis; Aouni, Mahjoub (Biomedicine & Healthcare Research, 2026)
Objectives: To characterize the mechanisms responsible for carbapenem resistance among a collection of Acinetobacter baumannii isolates recovered at the Tahar Sfar University hospital in Tunisia. Methods: Antimicrobial susceptibility testing were studied on Muller Hinton agar plates. Southern blot and PCR-based replicon typing (PBRT) were performed. Beta-lactamases genes were screened by PCR and sequencing. Conjugation experiments were carried out to determine whether the resistance determinants were transferable. Clonality of isolates was assessed by PFGE. Results: Sixteen carbapenem-resistant Acientobacter baumannii strains were collected over a 3-years period from patient hospitalized in different wards of the Tahar Sfar University hospital. Resistance to carbapenems was mostly due to the expression of the acquired blaOXA-23 and the intrinsic blaOXA-66 genes, both genes being associated with the ISAbaI insertion sequence. Mating-out assays showed that all carbapenem-resistant isolates carried the blaOXA-23 gene on plasmids that all belonged to the GR6 replicase group. Conclusions: This study reports on the molecular characterization of carbapenem resistance determinants in A. baumannii isolates. There is an urgent need for control measures to prevent dissemination of those multi-drug resistant strains.